Fractal patch antenna for GPS application - Murad, N.A.; Esa, M.; Yusof, S.K.; Fisal, Norsheila (2003)
Fractal patch antenna is proposed to reduce the size with miniaturization technique, not only for the single element structure, but also in an array design. This paper presents the design of fractal patch antenna based on the basic structure of square antenna operate at 1.575 GHz for global positioning system (GPS) application. The fractal design is introduced into the basic structure intended to reduce the frequency of operation. Hence, miniaturization can be achieved. Simulation has been performed on several sets of the design structures using ensemble SV software. The frequency imposed by the fractal structure is lower than the basic structure.